Investigative interviewing skills in policing: examining the transfer of training into workplace practices. Issue 3 (3rd September 2020) - Mount, David; Mazerolle, Lorraine
Abstract : Purpose: Police invest significant time, energy and resources to equip officers with the skills required to conduct effective investigative interviews. However, transferring those skills acquired or developed in a training environment for application in the police workplace is a journey fraught with impediments and diversions. Invariably, the quality and amount of skills transferred and applied on the job represent a paltry return on resource investment. This research explores the factors that impact the transfer of investigative interviewing skills from the training environment to the police workplace. Design/methodology/approach: Interviews with 40 officers, both uniformed and plain-clothes, were conducted to explore the influences on and impediments to effective skill transfer. Data were inductively analysed and thematically pattern-matched with existing research findings in the adult training domain. Findings: Results indicate that trainee motivation, perceptions of training relevance, perceptions of training quality and preparedness to conduct the task as trained directly and indirectly influence the degree to which investigative interviewing skills transfer from the training environment to the police workplace. Originality/value: This is original research in a domain that has previously received limited academic attention. An awareness of the factors that negatively impact on the transfer of acquired skills and ways to mitigate or ameliorate the detrimental effects are likely to assist police trainers and workplace managers to improve transfer rates and get more outcome value for the money, time and effort invested in training regimes.